(untitled) (Open Herald: Periodical of Methodical Research, 2024)
Academic literacy in foreign language teaching encompasses various crucial elements, with written speech occupying a prominent position within its framework. The significance of written communication cannot be overstated, as it serves as a fundamental pillar of academic discourse. Proficiency in writing effectively in a foreign language is an indispensable competence that university students must possess. This article aims to delve into the realm of academic literacy in foreign language teaching within the university context, shedding light on the pivotal role of written speech in its overall structure